2017
DOI: 10.3390/nano7120426
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Coated Iron Oxide Nanoparticles: A Promising Nanomaterial for Magnetic Hyperthermia Cancer Treatment

Abstract: Targeting cancer cells without injuring normal cells is the prime objective in treatment of cancer. In this present study, solvothermal and wet chemical precipitation techniques were employed to synthesize iron oxide (IO), hydroxyapatite (HAp), and hydroxyapatite coated iron oxide (IO-HAp) nanoparticles for magnetic hyperthermia mediated cancer therapy. The synthesized well dispersed spherical IO-HAp nanoparticles, magnetite, and apatite phases were confirmed by X-ray diffraction (XRD), Fourier-transform infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 41 publications
(36 reference statements)
3
66
0
2
Order By: Relevance
“…Nanocomposites made from magnetic material and certain non-magnetic biocompatible component are very important from the technological point of view. These materials include, for instance, coating of magnetic nanoparticles with polymer [15], synthetic silica [16], hydroxyapatite [17], and other different biocompatible materials. Among these, HAp/iron oxide nanocomposites attract great scientific attention.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites made from magnetic material and certain non-magnetic biocompatible component are very important from the technological point of view. These materials include, for instance, coating of magnetic nanoparticles with polymer [15], synthetic silica [16], hydroxyapatite [17], and other different biocompatible materials. Among these, HAp/iron oxide nanocomposites attract great scientific attention.…”
Section: Introductionmentioning
confidence: 99%
“…Our laser-assisted precipitation process is simple (one-pot) and rapid (short-time irradiation), and requires no surfactants. Therefore, it is advantageous over conventional fabrication processes of similar IO-CaP composite particles [14][15][16][17]. However, the IO-CaP submicrospheres fabricated by our process were inhomogeneous in their nanostructures (categorized as type A and type B).…”
Section: Discussionmentioning
confidence: 95%
“…CaPs are employed as a carrier matrix of IO nanoparticles, because they show low toxicity and good biocompatibility owing to their similarities to the mineral components found in human bones and teeth [10][11][12][13]. Conventionally, these IO-loaded CaP particles have been fabricated by time-consuming and/or multistep chemical precipitation processes [14][15][16][17]. For example, Mondal et al reported a two-step process in which IO nanoparticles were prepared and subsequently treated with CaP solutions to produce IO-loaded CaP particles [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanometer-sized particles have been a focus of intensive research in the biomedical field for applications such as drug delivery, clinical diagnostics, and biomedical imaging [ 1 , 2 , 3 , 4 , 5 , 6 ]. In order to raise diagnostic sensitivity and therapeutic efficiency, the ability to control and manipulate the interaction between cell membrane and nanoparticles (NPs) is required.…”
Section: Introductionmentioning
confidence: 99%